Isolation and Characterization of Mouse Coagulation Factor X – Biophysical and Enzymological Properties - James, H L; Larson, P J; Chao, Y B; Yan, S B; Kim, D J (Thrombosis and Haemostasis, 1997)
Mouse factor X was highly purified from plasma using barium ion precipitation and chromatography on anion-exchange and heparin- agarose affinity chromatography columns. Intact and reduced patterns of mouse factor X in SDS-PAGE were similar to those of human factor X. The specific absorption E 1%/1 cm at 280 nm of mouse factor X was found to be 11.2. Content of carbohydrate moieties of mouse factor X, determined to be 10% by weight, differs both quantitatively and quantitatively from that of human factor X, while the γ-carboxy- glutamic acid (Gla) and β-hydroxy-aspartic acid (β-OH-Asp) content were essentially the same as for human factor X. The amino-terminal amino acid sequences of the light and heavy chains of mouse factor X separated by SDS-PAGE were ANSFF--FKK and SVALXTSDSE, respectively. Underlined residues are non-identical with those of human factor X. Clotting time-based assays using human factor X- deficient plasma as substrate exhibited the following apparent extents of activation of factor X in mouse plasma, using human plasma as the standard: 195% (intrinsic); 200% (extrinsic); and 190% (RVV-X). Using the purified proteins in the same assay systems, the following apparent activation of mouse factor X was demonstrated, compared with human factor X: 195% (intrinsic); 27% (extrinsic); and 41% (RVV-X). These activity profiles suggest that the human extrinsic coagulation pathway functions less efficiently than the corresponding mouse pathway in the activation of mouse factor X. Furthermore, mouse brain thromboplastin satisfactorily replaced rabbit brain thromboplastin in extrinsic activation of factor X in mouse plasma, but not of human plasma or purified mouse or human factor X, in line with studies by others suggesting that human factor Vila poorly activates factor X in the presence of mouse tissue factor. While fully RVV-X-activated mouse factor X activated human prothrombin at a rate equal to about 117% of that for human factor X, it hydrolyzed the synthetic substrate, S-2222, at a rate of only about 18% of that for human factor X. These results are expected to be useful in making the mouse suitable for study of the mammalian blood coagulation pathways.